Pengaruh Modal Kerja dan Jumlah Anggota Terhadap Rentabilitas Koperasi - Raudatul Jannah; Menik Kurnia Siwi (Universitas Negeri Padang, 2020)
This study aims to determine: (1) the effect of working capital on profitability in a cooperative (2) the effect of numbers on profitability in a cooperative (3) the effect of working capital and the number of members on profitability in cooperatives. This type is descriptive causative research, the population used is all cooperatives in the city of Padang, the sample selection is determined using the purposive sampling method. The data collection technique used is documentation. The result showed that 1) working capital and the number of members had a significant effect on profitability whit a probability (F-statistic) of 0.000000<0.05. this means that working capital and the number of members have an effect on profitability in cooperatives. 2) working capital has a positive and insignificant effect on profitability in cooperatives whit a significant result of 0.0607>0.05. this shows that working capital has an effect on cooperative profitability. 3) the number of members has a positive and insignificant effect on profitability whit a significance of 0.5203>0.05. this means that the number of members has no effect on the cooperative’s profitability. Keywords: working capital, number of members, profitability